Meningkatkan Kesadaran Hukum di Kalangan Masyarakat Marginal Melalui Penyuluhan - Vina Hutama; Virly Vidiasti Sabijanto (Medan Resource Center, 2023)
In the context of Indonesia's social complexity, disparities in access to education and legal information result in marginalized communities being vulnerable to injustice. This article discusses the importance of enhancing legal awareness among marginalized communities through collaboration between government institutions, educational organizations, and civil society organizations. Legal education is identified as the primary solution to address these challenges. This collaboration yields a combination of expertise, resources, and networks that overcome the barriers to implementing legal education programs. The program elaborates legal concepts in simple language, empowers marginalized communities, and helps them understand the legal implications of their actions. Trust in the legal system is also built through this program, encouraging active participation in legal processes and enforcement.